Geologic controls on reservoir quality of the Viola limestone in Newbury field, Wabaunsee County, Kansas - McGuire, Creenen Ceddell (Kansas State University, 2019)
The focus of this study was Newbury field, Wabaunsee County, Kansas, and the geologic controls that allow for economic oil production from the Viola formation. Newbury field has produced 507,894 barrels of oil from the Viola formation between 1965 and 2018 (Newbury—Oil and Gas Production, 2018). The Viola formation’s favorable reservoir characteristics have drawn production interest in Nebraska, Kansas, and Oklahoma, with 50 fields producing oil along the boundary of the Forest City basin and Nemaha ridge (Dolton and Finn, 1989). The Viola formation is a Middle to Upper Ordovician age carbonate composed of dolomite, chert, and limestone (Adkinson, 1972). South of Newbury field are the Davis Ranch and John Creek fields. Davis Ranch and John Creek are the two largest fields along the western boundary of the Forest City basin in northeastern Kansas. Davis Ranch and John Creek have produced 9,084,020 and 10,305,259 barrels of oil, respectively, from the Viola formation (Davis Ranch—Oil and Gas Production, 2018; John Creek—Oil and Gas Production, 2018). So, what geologic controls allow for such variation in production from the Viola formation within the Forest City basin of northeastern Kansas? Two previous studies of the Soldier and Leach fields, which are northeast of the Newbury field, showed that production there has been less than that of Newbury field (Jensik, 2013; Rennaker, 2016). These studies reported that Viola reservoir quality is controlled by dolomitization (Jensik, 2013; Rennaker, 2016), because areas of dolomitization showed greater porosity and permeability, which in turn results in more favorable reservoir characteristics (Jensik, 2013; Rennaker, 2016). To understand this variation in production quality from the same formation, geologic controls of the Viola formation in Newbury field were identified using well log analysis; binocular and petrographic microscopy; alizarin red staining, subsurface mapping, and reserve calculations. Several conclusions that will aid geologists to more easily identify economically viable Viola formation reservoirs along the western edge of the Forest City basin were drawn from this study. Production variation between fields in the Forest City basin is controlled not only by structure, but also by porosity. Viola formation porosity varies with spatial distribution due to varying degrees of dolomitization. Degree of dolomitization controls dolomite crystal size and dolomite texture, and thus controls porosity. Porosity is also affected by large scale fracture networks due to the proximity of the Nemaha Uplift. Production within Newbury field varies due to structure, but also from differences in dolomite crystal size and texture, and thus porosity. Wells in Newbury field with smaller dolomite crystal size ranges and euhedral to subhedral textures have slower, but longer production, while wells with large dolomite crystal size ranges, and euhedral to anhedral textures have short lived production.
Keywords: Geologic controls; Viola formation; Viola limestone; Newbury field; Forest City basin